Study of dermatoglyphics in type 2 diabetic individuals in a teaching hospital, Telangana (Panacea Journal of Medical Sciences, 2021)
Background: Dermatoglyphic pattern, epidermal ridges found in the fingertips of the palm exhibits in various pattern like whorl, arch and loop. This pattern of arrangement develops by 22nd weeks of intrauterine life and persists all through the life without any change. Among the metabolic disorders available globally, Dermatoglyphics as a diagnostic aid is now well established in number of diseases which have strong hereditary basis and is employed as a method for screening for abnormalities.Aim of the study: To study dermatoglyphics in type 2 diabetic individuals.Materials and Methods: Prospective observational study for duration of one year from March 2019 to February 2020 at the Department of Forensic Medicine at Maheshwara Medical College and Hospital, Patancheru, Telangana. Dematoglyphics were studied in 50 known cases of type 2 diabetes mellitus and compared with normal, healthy, non diabetic age matched control individuals. The patterns on both palms were recorded by the Modified Ink Method and studied for finger tip pattern configuration, palmar pattern configuration, palmar a-b ridge counts and palmar atd angle.